Double Transplanting- A Indigenous Technology Practiced By Tribal Farmers to Combat Aberrant Climatic Condition - Kumar, Das Tarun; Tanmay, Samajdar; Biplab, Mitra; Greatush, Marak (Indian Journal of Hill Farming, 2018)
The state Meghalaya has diversified topography, altitude and climatic conditions and it is dominated by tribal indigenous communities. Rice is the main crop in the state during monsoon season. In the Garo Hills region, a large proportion of rice land is under medium and low-lying areas, which are subjected to the risk of flood due to heavy rains within a short span of time. To recover of yield losses, the tribal farmers started practicing of a indigenous technology i.e. double transplanting. During kharif 2015, sixty farmers practicing double transplanting system were selected from Garo Hills to assess the benefit of the technology in real farming situation. The data, collected through survey and focus group discussion with key informants, revealed that average yield obtained under double transplanting (41.5 q/ha) was 83% higher than the average yield achieved with single transplanting. This was primarily due to more vigorous seedlings leading to higher tillering ability (10-12/plant against 6-7 under single transplanting) with more number of panicles (240-280/sq. m.). Despite the higher cost of cultivation, double transplanting recorded the maximum net return (Rs. 30950.00/ha) as well as benefit-cost ratio (1.99).